Expression of apomixis genes during reproductive development in Urochloa decumbens and Urochloa ruziziensis (Poaceae) - Mara Jane da Rocha; Ana Gabriela Damasceno; Rubens Diogo Junior; Heloisa Oliveira dos Santos; Fausto Souza Sobrinho; Vânia Helena Techio; Welison Andrade Pereira (Acta Scientiarum. Agronomy, 2026)
This study aimed to correlate the developmental stages of the embryo sac with the morphometric traits of spikelets and to characterize the expression of the BbrizRan, BbrizSti1, and BbrizAGL6 genes in Urochloa ruziziensis (sexual) and U. decumbens (apomictic). Data on the length and diameter of spikelets and anatomical sections were also obtained. Gene expression was determined using RT-qPCR in spikelets at megasporogenesis and megagametogenesis. The spikelet length could be used as a reliable morphological marker to discriminate between the two stages in both species. The embryo sacs observed were of the Polygonum type in U. ruziziensis and the Panicum type in U. decumbens. RT-qPCR analysis revealed that the BbrizRan, BbrizSti1, and BbrizAGL6 genes were differentially expressed in the studied species during reproductive development. The BbrizSti1 gene was more highly expressed in U. decumbens (apomictic) than in U. ruziziensis (sexual) during megasporogenesis, while for BbrizRan, U. decumbens showed higher expression than U. ruziziensis during both megasporogenesis and megagametogenesis. An increase in the expression level of BbrizAGL6 was observed in both species at both developmental stages of the embryo sac.